Theoretical Analysis of S, M and N Structural Proteins by the Protein–RNA Recognition Code Leads to Genes/proteins that Are Relevant to the SARS-CoV-2 Life Cycle and Pathogenesis - Nahalka, Jozef (Frontiers in Genetics, 2021)
In this conceptual review, based on the protein–RNA recognition code, some theoretical sequences were detected in the spike (S), membrane (M) and capsid (N) proteins that may post-transcriptionally regulate the host genes/proteins in immune homeostasis, pulmonary epithelial tissue homeostasis, and lipid homeostasis. According the review of literature, the spectrum of identified genes/proteins shows that the virus promotes IL1α/β–IL1R1 signaling (type 1 immunity) and immunity defense against helminths and venoms (type 2 immunity). In the alteration of homeostasis in the pulmonary epithelial tissue, the virus blocks the function of cilia and the molecular programs that are involved in wound healing (EMT and MET). Additionally, the protein–RNA recognition method described here identifies compatible sequences in the S1A-domain for the post-transcriptional promotion of PIKFYVE, which is one of the critical factors for SARS-CoV-2 entry to the host cell, and for the post-transcriptional repression of xylulokinase XYLB. A decrease in XYLB product (Xu5P) in plasma was proposed as one of the potential metabolomics biomarkers of COVID-19.